Accessible Science Learning for Deaf Students in Inclusive Elementary Classrooms: Teaching Strategies, Communication Barriers, and Support Needs - Made Shinta Wesiana Dewi; Putu Nanci Riastini; I Wayan Ardana (Universitas Pendidikan Ganesha, 2026)
Deaf students in inclusive elementary schools often experience barriers in science learning because verbal explanations, abstract concepts, and science terminology are not always accessible through conventional classroom practices. This study aimed to describe the science learning process for deaf students at SD Inklusi Negeri 2 Bengkala, focusing on teaching strategies, learning challenges, media use, classroom interaction, and the role of the special mentor teacher. A descriptive qualitative design was employed. Data were collected through classroom observation, semi-structured interviews, and document study involving regular teachers, special mentor teachers, hearing students, and deaf students. The data were analyzed through data reduction, data display, and conclusion drawing. The findings showed that science learning was implemented through expository teaching, contextual learning, demonstration, role-play, visual media, and sign-language assistance. The main challenges faced by deaf students included difficulty understanding verbal explanations, limited access to science terminology in sign language, inadequate assistive technology, dependence on the special mentor teacher, and limited participation in discussion-based learning. The study concludes that inclusive science learning requires stronger visual support, adaptive media, sufficient special mentor teacher assistance, and more interactive learning strategies.